Optimization Combining with Digital Transformation of the Men's Shirts Processing at Small and Medium-Sized Garment Enterprises in Vietnam - Le, Tieu-Thanh; Bui, Phuong-Thao Thi; La, Ngoc-Anh Thi; Dang, Thai-Viet (International Journal of Robotics and Control Systems, 2024)
Industry 4.0 has become a hype among the manufacturing industries across the globe. Recent developments require significant capital investments, but these technologies are yet to be established in developing countries such as Vietnam, especially the apparel industry.  Based on a survey of the current situation at small and medium-sized enterprises in Vietnam's textile industry, the paper proposes to apply technology, test and evaluate the effectiveness of applying and coordinating digital systems in management and chain supply. Multifaceted applications have been specifically explored including automatic equipment and digital systems, spanning the domains of automation, robotics, artificial intelligence, data analytics, and the Internet of Things (IoT). These technologies are posited as catalysts for transformative improvements in production efficiency and resource utilization. Furthermore, experimental results point out the symbiotic relationship between technology adoption and effective management strategies to achieve holistic operational enhancements.  As the Vietnamese textile industry strives for competitive excellence in the global arena, this research offers actionable insights for industry practitioners, policymakers, and researchers.